Implementation Problem Solving in Archaebacteria and Eubacteria Concept to Increased Activity and Student Learning Outcome - Hayati, Nida; Putra, Aminuddin P. (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
Research on increased activity and student learning outcomes have been made to the students of Grade X MIA 2 SMAN 5 Banjarmasin on Archaebacreria And eubacteria. This study aims to increase student activity, student learning outcomes, teacher activity and student responses on the class X MIA 2 SMAN 5 Banjarmasin to learning materials archaebacteria and eubacteria using Problem Solving learning model. The research was descriptive with classroom action research (PTK) with a research subject is class X MIA 2 SMAN 5 Banjarmasin. The results showed that the learning model of Problem Solving in archaebacteria and eubacteria material can enhance the activity of students with grades in the first cycle ie 95.05% on sikus II acquired 98.88%. Teacher activity decreased from the first cycle to the second cycle of 100% and 85%. Classical completeness results on the first cycle has an average value of 25%, while in the second cycle increased ie 87.67% of the data obtained shows the achievement of classical completeness is set at â‰¥ 85%. During the learning process of students in the first cycle has an average value of 66.24%, while the second cycle is 86.18% with the good category. Student responses using Problem Solving learning model states 45.89% agree.Keywords:Â Problem Solving, Activities, Learning Outcomes and archaebacteria and eubacteria, characteristics and roles